2021
DOI: 10.3390/ani11041105
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Approach to Comparing Thermal Activity of the Thoracic Region and Saddle Pressure Distribution beneath the Saddle in a Group of Non-Lame Sports Horses

Abstract: Thermography is a non-invasive method for measuring surface temperatures and may be a convenient way of identifying hypo/hyperthermic areas under a saddle that may be related to saddle pressures. A thermal camera quantified minimum/maximum/mean temperatures at specific locations (left/right) of the thoracic region at three-time points: (1) baseline; (2) post lunging; (3) post ridden exercise in eight non-lame sports horses ridden by the same rider. A Pliance (Novel) pressure mat determined the mean/peak saddle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…No association was found between the thermographic images and the pressure obtained by the sensors. Only one previous study was found where the relationship between thermal activity and pressure on the back was evaluated with sensors and, with similar results as in this study (Mackechnie-Guire et al, 2021). Thermography and pressure sensors have been used as a practical tool to assess saddle fit in equines, by measuring the magnitude, pressure distribution, increased metabolic activity, and skin blood flow (Desbrosses-Déléage et al, 2019;Soroko et al, 2018).…”
Section: Variablesupporting
confidence: 69%
“…No association was found between the thermographic images and the pressure obtained by the sensors. Only one previous study was found where the relationship between thermal activity and pressure on the back was evaluated with sensors and, with similar results as in this study (Mackechnie-Guire et al, 2021). Thermography and pressure sensors have been used as a practical tool to assess saddle fit in equines, by measuring the magnitude, pressure distribution, increased metabolic activity, and skin blood flow (Desbrosses-Déléage et al, 2019;Soroko et al, 2018).…”
Section: Variablesupporting
confidence: 69%
“…Such assessment, following Dyson et al [ 30 ], should be useful in the everyday equine practice, where a horse performs the under-rider overground exercise with turns and circles. As the practical application of modern technologies is developing dynamically both in the field of equine thermal imaging [ 62 , 63 , 64 ] and DIP of medical images [ 31 , 33 , 36 , 37 , 38 , 39 , 40 ], each new approach can ultimately reach every horse owner.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the main limitation of this study is disregarding the evaluation of horse’s emotions and horse’s experiences and therefore should be considered as preliminary. In further research, the rider position in the saddle, as a function of rider size and skill [ 30 ], the effect of inappropriate saddle fit [ 42 , 64 , 68 ], the impact of different environmental conditions [ 21 , 54 , 55 ], and most importantly an evaluation of the equine behavior indicative of underlying mood state and general well-being of horses [ 9 , 15 , 16 ] should be considered to explain the role of this horses:human interaction assessment in the overall improvement of the equine quality of life.…”
Section: Discussionmentioning
confidence: 99%